ANALISIS PENERAPAN PENCATATAN DAN PELAPORAN KEUANGAN MASJID DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS ( Studi Pada Masjid Besar Nurul Jama’ah Kec. Tanah Merah ) - Nurhabiba, Nurhabiba; Usdeldi, Usdeldi; Marissa Putriana (Nusantara Hasana Journal, 2026)
Mosque financial management plays an important role in maintaining the trust of the congregation as the party providing funds. This study aims to analyze the practices of mosque financial recording and reporting in improving transparency and accountability at the Grand Mosque of Nurul Jama’ah. The focus of the study includes financial transaction recording and financial reporting. This research uses a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The research informants consist of mosque administrators and congregation members. The data were analyzed by describing the financial management practices implemented in the field and examined using Practice-Based Financial Reporting Theory. The results of the study show that mosque financial recording is carried out in a simple manner using a single cash book with a single-entry system, where all receipts and expenditures are recorded chronologically and supported by transaction evidence. Financial reports are delivered regularly to the congregation every Friday through direct announcements and the mosque information board. However, the recording and reporting of mosque assets have not been carried out systematically, so financial information is still limited to cash aspects. Nevertheless, these financial management practices reflect the mosque administrators’ efforts toward transparency and accountability to the congregation.